2013
DOI: 10.4322/polimeros.2013.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of soy lecithin and Yucca schidigera extract on the properties of gelatin and glycerol based biodegradable films.

Abstract: Gelatin-based films containing soy lecithin or Yucca schidigera extract and glycerol as plasticizer were produced by casting and characterized for their mechanical properties, water vapor permeability (WVP), water solubility, opacity and morphology. The addition of glycerol reduced the tensile strength, with a difference of ~ 68% between the values for the minimum and maximum concentrations evaluated, both for the plasticizer and the surfactant. Elongation values reached 52% and 40%, for films containing yucca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…However, the results of this study were higher than synthetic films, such as high-density polyethylene film (HDPE) (0.0012 g.mm/h m 2 kPa) and polyester film (0.0091 g.mm/kPa h m 2 ) [32] . Dias et al [33] obtained similar values to those found in this work (0.21 to 0.24 g.mm/h m 2 kPa) for films of pig hide gelatin and glycerol containing yucca extract and lecithin respectively.…”
Section: Water Vapor Permeability (Wvp)supporting
confidence: 80%
See 1 more Smart Citation
“…However, the results of this study were higher than synthetic films, such as high-density polyethylene film (HDPE) (0.0012 g.mm/h m 2 kPa) and polyester film (0.0091 g.mm/kPa h m 2 ) [32] . Dias et al [33] obtained similar values to those found in this work (0.21 to 0.24 g.mm/h m 2 kPa) for films of pig hide gelatin and glycerol containing yucca extract and lecithin respectively.…”
Section: Water Vapor Permeability (Wvp)supporting
confidence: 80%
“…Ma et al [41] , reported that the presence of olive oil led to the marked increases in the roughness of the films. The increase in the surface roughness is principally due to the adherence and formation of oil droplets [33] .…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Rodriguez et al [19] found a synergistic behaviour (lower tensile strength, higher elongation and higher water vapour permeability, WVP) between glycerol (as plasticiser) and emulsifiers, such as Tween 20, Span 80 and soybean lecithin, in potato starch films. Finally, Dias et al [20] used glycerol as the plasticiser in gelatin-based films containing Yucca schidigera extract and lecithin, respectively. They obtained solid, flexible films with low WVP and concluded that addition of other emulsifiers commonly associated with plasticisers typically used in the production of edible and biodegradable films should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…De forma geral, os filmes biodegradáveis se caracterizam por serem materiais higroscópicos, ou seja, sensíveis à umidade do ar, o que afeta suas propriedades mecânicas, limitando suas aplicações comerciais (ANDREUCCETTI; CARVALHO; GROSSO, 2010;DIAS et al, 2013;GENNADIOS et al, 1994). Em busca de melhorar as propriedades físicas dos filmes biodegradáveis, diferentes alternativas têm sido estudadas, tais como a utilização de novos plastificantes, hidrofílicos (ex.…”
Section: Introductionunclassified